The influence of emotional stimuli on response inhibition: a systematic review in non-clinical adults - Rincón-Pérez, Irene; Sánchez-Carmona, Alberto J.; Levy, David; López-Martín, Sara; Hinojosa, José A.; Albert, Jacobo (Frontiers in Psychology, 2025)
This PRISMA-compliant systematic review aimed to clarify the influence of emotional stimuli on the behavioral correlates of response inhibition, given the mixed and inconclusive findings in the existing literature. We searched Scopus, PsycINFO and PubMed databases up to March 2024 for studies published in peer-reviewed journals, conducted in adult non-clinical populations. Eligible studies used tasks where response inhibition plays a central role (primarily the Go/No-Go task [GNG] and stop-signal task [SST]) and included emotional stimuli presented concurrently with the task. Additionally, studies had to report, control for, analyze, or at least discuss both valence (positive-negative) and arousal (calming-arousing), two emotional dimensions that have been widely used to define emotions. Ninety-three studies, encompassing over 3,400 participants, were finally included, and assessed using the Appraisal tool for Cross-Sectional Studies (AXIS). Most studies report emotional modulation of response inhibition, with a larger proportion linking this influence to valence rather than arousal. However, inconsistent findings and methodological limitations prevent firm conclusions, with some suggesting the involvement of both or neither dimension, while others lack the appropriate design. Among studies reporting effects of emotional valence, most indicate that higher valence stimuli (more positive) impaired response inhibition. The effects of arousal remain unclear, with some studies linking high arousal to poorer inhibition, while others suggest the opposite. Interestingly, discrete emotions also modulate response inhibition independently of valence and arousal, suggesting that discrete emotion theories may complement the two-dimensional circumplex model in response inhibition research. While few differences exist, more studies report effects when emotional stimuli are task-relevant rather than task-irrelevant. Among other factors, using an SST instead of a GNG task seems to enhance emotional modulation of response inhibition. Overall, the influence of emotional stimuli on the behavioral correlates of response inhibition is likely shaped by a complex interplay of multiple factors, suggesting that future research should explore how these factors interact and combine. Moreover, further research is needed to explore how emotion interacts with other forms of inhibitory control beyond global reactive inhibition, including proactive and selective mechanisms.